Aesthetic Rehabilitation of Maxillary Anterior Teeth Following Internal Bleaching with Direct Composite Veneers: Aesthetic Rehabilitation of Maxillary Anterior Teeth - Meuthia Sari; Hendra Dian Adhita Dharsono; Dudi Aripin (SONDE (Sound of Dentistry), 2026)
Background: Intrinsic discoloration often present significant aesthetic challenges, particularly in patients with a history of an inadequate endodontic treatment. In such cases, a combining internal bleaching, endodontic therapy, and aesthetic rehabilitation is required to restore both function and appearance. This minimally invasive approach supports long-term aesthetic outcomes while preserving tooth structure. Objective: To present the management of intrinsic discoloration and anterior tooth asymmetry using internal bleaching, endodontic retreatment and direct composite veneers. Case Report: A 24-year-old female came to the Department of Conservative Dentistry, Padjadjaran University presented with discoloration of tooth 21, which had undergone an inadequate endodontic treatment several years using a zinc oxide-based root filling material. Internal bleaching was performed using the walking bleach technique with 35% hydrogen peroxide. Meanwhile, on tooth 11 presented with a periapical abcess and root canal treatment was presented. After achieving a shade match, old composite restoration on teeth 11,21 were removed and replaced with new direct composite veneers. Additionally, both maxillary lateral incisors received direct composite veneers to correct tooth shape and achieve aesthetic balance. Results: The combination of internal bleaching and endodontic retreatment successfully eliminated the discoloration and resolved the infection. Composite veneers provided an aesthetically pleasing and balanced outcome. Conclusion: Internal bleaching, when combined with endodontic therapy and direct composite veneers, offers a conservative and effective solution for managing complex anterior aesthetic cases. Addressing both discoloration and morphological imbalance can significantly improve the final aesthetic outcome.